Ethics and professionalism - Kultgen, John H. (UPCC book collections on Project MUSE., 1988)
John Kultgen explores the ways morality and professional ideals are connected. In assessing the moral impact of professionalism in our society, he examines both the structure and organization of occupations and the ideals and ideology associated with professions.Differing from standard treatments of professional ethics, Ethics and Professionalism recognizes that it is the practices within the professions that determine whether rules and ideals are used as masks for self-interest or for genuinely moral purposes.